Changes in structure and conduction type upon addition of Ir to ZnO thin films - Zubkins, Martins; Kalendarev, Robert; Gabrusenoks, Jevgenijs; Plaude, A. V.; Zitolo, Andrea; Anspoks, Andris; Pudzs, Kaspars; Vilnis, Kaspars; Azens, Andris; Purans, Juris (Elsevier B.V., 2017)
Zn-Ir-O (Zn/Ir ≈ 1/1) thin films have been reported to be a potential p-type TCO material. It is, however, unknown whether it is possible to achieve p-type conductivity at low Ir content, and how the type and the magnitude of conductivity are affected by the film structure. To investigate the changes in properties taking place at low and moderate Ir content, this study focuses on the structure, electrical and optical properties of ZnO:Ir films with iridium concentration varying between 0.0 and 16.4 at.%. ZnO:Ir thin films were deposited on glass, Si, and Ti substrates by DC reactive magnetron co-sputtering at room temperature. Low Ir content (up to 5.1 at.%) films contain both a nano-crystalline wurtzite-type ZnO phase and an X-ray amorphous phase. The size of the crystallites is below 10 nm and the lattice parameters a and c are larger than those of pure ZnO crystal. Structural investigation showed that the film's crystallinity declines with the iridium concentration and films become completely amorphous at iridium concentrations between 7.0 and 16.0 at.%. An intense Raman band at approximately 720 cm− 1 appears upon Ir incorporation and can be ascribed to peroxide O22– ions. Measurable electrical conductivity appears together with a complete disappearance of the wurtzite-type ZnO phase. The conduction type undergoes a transition from n- to p-type in the Ir concentration range between 12.4 and 16.4 at.%. Absorption in the visible range increases linearly with the iridium concentration.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Amorphous doped ZnO; Iridium; Reactive DC magnetron co-sputtering; Thin films